2019
DOI: 10.1186/s12883-019-1320-8
|View full text |Cite
|
Sign up to set email alerts
|

The development and feasibility of treadmill-induced fall recovery training applied to individuals with chronic stroke

Abstract: Background Exercise has failed to reduce falls in those with chronic stroke. A limitation of traditional exercise is that the motor responses needed to prevent a fall are not elicited (i.e. they lack processing specificity ). Balance reactions often require compensatory steps. Therefore, interventions that target such steps have the potential to reduce falls. Computerized treadmills can deliver precise, repeatable, and challenging perturbations as part of a training prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…Few adverse events from PBT training have been reported in the literature. Most studies report no or relatively minor adverse events such as soreness at the contact points between the body and the harness or muscle soreness ( 156 – 160 ). In 12 RCTs ( 20 , 36 , 52 , 97 , 122 , 159 , 161 165 ) summarized by Mansfield et al ( 166 ), pain and delayed onset muscle soreness were the most commonly reported adverse events (16.4% of participants), with no severe adverse events reported in these trials.…”
Section: Implementation In Practicementioning
confidence: 99%
“…Few adverse events from PBT training have been reported in the literature. Most studies report no or relatively minor adverse events such as soreness at the contact points between the body and the harness or muscle soreness ( 156 – 160 ). In 12 RCTs ( 20 , 36 , 52 , 97 , 122 , 159 , 161 165 ) summarized by Mansfield et al ( 166 ), pain and delayed onset muscle soreness were the most commonly reported adverse events (16.4% of participants), with no severe adverse events reported in these trials.…”
Section: Implementation In Practicementioning
confidence: 99%
“…The ability to dynamically adapt locomotion is critical for maintaining balance. In the event that one slips or trips, a quick adjustment must be made in order to maintain balance 1 , 2 . New locomotor patterns must also be adopted to safely navigate along a narrow path 3 or on uneven terrain 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, feet-in-place balance reactions can be improved over the course of five practice sessions in children with CP. 7 Other forms of perturbation-based training can be translated from previous applications in stroke rehabilitation, including large treadmill-induced perturbations from our own studies, 38 as well as more clinically feasible versions involving lean-releases and therapist-induced perturbations. 39 In the context of interventions, the capabilities that we have quantified in the present study can serve as a modifiable target for interventions to improve that skill and, potentially, alter the risk of falling.…”
Section: Discussionmentioning
confidence: 99%